Partisipasi Awam dalam Penggalian Hukum Islam (Studi Analisis Proses Pencarian 'Illat dan Hikmah Hukum Sebagai Proses Penelitian Ilmiah) - Ahmad Mujalli (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2015)
: Lay participation can be the alternative in the details of law excavation process (istinbath law) to form a Fiqh characters which are righteous likulli zaman wa makan. Since the main character of the discourse of the fiqh never irrespective from the change and development, its changing goes along with the world changing and develops by following the development of the universe. Basically the Islamic law excavation rooted in the searching process of 'illat and legal wisdom (Masalik' illat and wisdom). Before the legal was set, the motive behind every legal regulation was first looked. Whether the motive is on the worship or people benefit motive, as well as other motives. Masalik 'illat and wisdom contain research process just like other the research processes. In the context of tahqiqul manath (such as the dangerous of smoking) lay people can participate, while in the context of takhriij al-Manath (for instance any harmful thing is forbidden) becomes purely jurists' competence. And with this lay khash involvement, fiqh formula product (is expected) to really run in accordance with the will of the shari'ah and in line with the will of the benefit of the people.